The influence of the European Union on Turkish foreign policy - Terzi, Özlem (Routledge, 2016)
EU membership provides member states with a new perception of their place in the world; their foreign policies very much influenced by their involvement in the politics of Brussels. The candidate countries also go through the same experience. The membership prospect however, presented a serious challenge to Turkish foreign policy and it was obvious from the moment Turkey was declared as a candidate country in 1999 that its membership perspective was linked to the solution of problems in its domestic and foreign relations. In this book, Özlem Terzi examines the influence of the European Union on the making of Turkish foreign policy since it was declared a candidate country. By comparing an issue specific analysis alongside an actor-based focus, Terzi questions whether such a transformation in the self-perceptions of Turkish policy makers is actually taking place, and whether the policy making process with respect to foreign policy issues expands to include new actors, like the civil society, thus democratizing the way foreign policy is made. Case study rich and packed with interviews with actors involved in policy making in Brussels and Ankara, this book enables the reader to correctly discern the factors that make the Turkish case unique and to reveal whether certain aspects of Turkey's pre-accession process are not as unique as we think. 'The Influence of the European Union on Turkish Foreign Policy' is a valuable and informative contribution for students, researchers and scholars interested on the transformative power of the EU and the role of Turkey's relationship with its neighbours.